Virtual data generation with kitchen objects for training neural networks - Fañanás Anaya, Javier; López-Nicolás, Gonzalo; Sagüés, Carlos (Jornada de Jóvenes Investigadores del I3A, 2023)
Neural network-based vision algorithms require large amounts of precisely labeled data. Obtaining this data manually is a very time consuming process. In this work we propose to use game engines to generate automatically labeled images for training neural networks.